Responsible Research and Innovation Actions in Science Education, Gender and Ethics Cases and Experiences - Ferri, Fernando (SpringerBriefs in Research and Innovation Governance,, 2018)
This book gathers case studies presented at the International Conference on Responsible Research and Innovation in Science, Innovation and Society (RRI-SIS2017). It highlights European initiatives and projects in various domains and contexts, each of which explores how to create guidelines and good practices for Responsible Research and Innovation and how to promote them among citizens, industry stakeholders, policy and decision makers, research funders and educational institutions to foster their adoption as a potential benchmark in establishing RRI processes. Further, the book discusses gender and ethical issues, which are highly relevant for RRI initiatives in connection with representativeness, risks and in some cases, minority rights.